The Challenges of repackaging Traditional Knowledge in the Context of Intellectual Property Rights : Case of Zimbabwe and Uganda - Chisita, Collence; Kaddu, Sarah (International Conference on Knowledge Management, 2009)
This paper is based on two case studies of Uganda and Zimbabwe. It gives a brief overview of Traditional Knowledge (TK) and defines the key concepts: TK/IK, Intellectual Property and repackaging of information. Through observation, face to face interviews and literature analysis, the paper discusses: Role of Higher Education Institutions in promoting TK, challenges of TK with special reference to challenges related to characteristics of TK, Challenges of protecting TK and Challenges of Repackaging TK. The paper further discusses women’s role in the preservation of TK and the reasons why traditional knowledge is lowly appreciated with recommendations towards repackaging traditional knowledge to spur development